Microstructure development during pyrolysis of wet-laid nonwoven-based CFRP for the manufacturing of ceramic matrix composites (CMC) - Fiona Kessel; Luis Baier; Nils Hensch; Martin Frieß; Anna Markic; Thomas Bratzdrum; Dietmar Koch (Open Ceramics)
Fiber reinforcement plays a critical role in defining the properties of ceramic matrix composites (CMCs). Among various textile technologies, wet-laid nonwovens have gained attention because previous studies have shown that their method of production significantly influences ceramic formation during liquid silicon infiltration (LSI) [1]. This study investigates in-situ microstructural evolution during pyrolysis using microscopy in a small-scale furnace. Two carbon fiber-reinforced polymer (CFRP) types were examined: single filament and fiber bundle wet-laid nonwovens. Thermal analysis revealed distinct behaviors. In single filament samples, key cracking occurred around 610 °C due to matrix weakening and stress release. In contrast, fiber bundle samples showed crack formation at 150–300 °C and above 700 °C, driven by outgassing, partial matrix detachment, and matrix shrinkage. These mechanisms result in SiC-rich structures for single filament reinforced materials and carbon-rich, short fiber composites for bundle reinforced materials. The findings support tailored reinforcement design for application-specific CMC properties.